Analysis of Emotions and Dysfunctional Attitudes in Depression. (31st August 2018) - Tehranchi, Ata; Neshatdoost, Hamid Taher; Amiri, Shole; Power, Mick
Abstract: The current study was designed to examine the role of basic emotions and dysfunctional attitudes in depression. Moreover, six models related to the organization of emotions were examined through confirmatory factor analysis. Two hundred individuals with major depressive disorder were recruited from three clinical psychology centers. Participants completed a battery of questionnaires measuring basic emotions, dysfunctional attitudes, and depressive. Results demonstrated that the dysfunctional attitude of "need for approval" and the basic emotions of disgust and sadness could predict depressive scores positively and significantly. It was also shown that the dysfunctional attitudes could positively and significantly predict the two negative emotions of disgust and sadness. Thus, the findings supported an analysis in which the two basic emotions of sadness and disgust were elevated in individuals with depressive disorders. Confirmatory factor analysis supported the proposed basic emotions model and did not support alternative models, such as the positive affect and negative affect model.